Environmental engineering education for sustainable development in IIUM - Jami, Mohammed Saedi; Muyibi, Suleyman Aremu; Al-Mamun, Abdullah (2011)
The purpose of this paper is to discuss the necessity and benefit of environmental engineering education for sustainable development and initiate some practical activities in the context of International Islamic University Malaysia. Brief introduction about the university is included focusing on pertinent environmental issues. Following the overview will contain the faculties and departments related to environment. And to capture the relationship between the overview and the environmental situation, the paper will focus deeply on the proposed strategies to address the campus sustainability issues. Recommendations are given to improve the awareness of the university community (students, academic and non academic staffs, etc). Also included are expected problems and possible solutions.